2013
DOI: 10.1111/1365-2435.12095
|View full text |Cite
|
Sign up to set email alerts
|

Allocating CSR plant functional types: the use of leaf economics and size traits to classify woody and herbaceous vascular plants

Abstract: Summary1. Three main directions of adaptive specialization are evident in the world flora, reflecting fundamental trade-offs between economics (conservative vs. acquisitive investment of resources) and size. The current method of ordinating plants according to these trade-offs, CSR classification, cannot be applied to the woody species that dominate many terrestrial ecosystems. 2. We aimed to produce a novel CSR classification method applicable to vascular plants in general.3. Principal components analysis (PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
279
1
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 263 publications
(304 citation statements)
references
References 42 publications
9
279
1
15
Order By: Relevance
“…The positions signalled by numbers 3, 4, and 5 in Fig. 2a (and described in Extended Data Table 2) could arguably roughly correspond to the stress-tolerant, ruderal, and competitor strategies of Grime 3,11,19 . Interestingly, the functional hotspots lie at intermediate positions on the plane rather than at any of these extreme positions (that is, r versus K, acquisitive versus conservative resource economy, C, S or R-strategy).…”
Section: Discussionmentioning
confidence: 88%
“…The positions signalled by numbers 3, 4, and 5 in Fig. 2a (and described in Extended Data Table 2) could arguably roughly correspond to the stress-tolerant, ruderal, and competitor strategies of Grime 3,11,19 . Interestingly, the functional hotspots lie at intermediate positions on the plane rather than at any of these extreme positions (that is, r versus K, acquisitive versus conservative resource economy, C, S or R-strategy).…”
Section: Discussionmentioning
confidence: 88%
“…Apart from leaf size, 'economics' traits form a major axis of variability in vascular plant phenotypes globally known as the 'worldwide leaf economics spectrum' (Wright et al 2004). This spectrum reflects a gradient of acquisitive to conservative resource investment strategies evident in resource-rich to resource-poor habitats, and consistently emerges in multivariate analyses of plant traits (Díaz et al 2004;Cerabolini et al 2010;Frenette-Dussault et al 2012;Freschet et al 2012;Pierce et al 2013). At the 'acquisitive' end of this spectrum are leaves with high specific leaf area (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Primary strategies are essentially suites of traits that impact on key functions allowing survival, and involve the investment of photosynthates and mineral nutrients in three principal activities: further growth, the maintenance and protection of metabolic processes, or reproduction (Grime and Pierce 2012). Strategies thus represent a three-way investment trade-off between traits facilitating these competing functions: a trade-off that has been recorded repeatedly in large scale studies of wild plants (Díaz et al 2004;Cerabolini et al 2010;Frenette-Dussault et al 2012;Pierce et al 2013). These three principal extremes of adaptive specialization are predicted by Grime's (2001) competitor, stress-tolerator, ruderal (CSR) plant strategy theory and its successor, universal adaptive strategy theory (Grime and Pierce 2012), in which C-selected 'competitors' maximize growth by using large physical size (large leaves and root systems, tall canopies) to acquire resources and dominate stable, resource-rich niches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown ambiguous results in relation to apply the CSR model, especially to woody species (Pierce et al, 2013). Navas et al (2010) used revised categories for lateral spread proposed by Grime et al, (2007) to modify CSR classification and include woody species.…”
Section: Introductionmentioning
confidence: 99%